Study of the electronic stopping power of proton in different materials according to the Bohr and Bethe theories - Alruhaimi Shahla A. S.; Tarkhan Widad Hamza; Hussien Ahlam Habeeb (Open Engineering, 2025)
In this research, a theoretical study was conducted to calculate the electronic stopping force using the Bohr and Bethe equations for charged particles (protons) located on the elements (13Al, 14Si, 29Cu, 32Ge, 47Ag, 78Pt, 79Au, and 82Pb) within the energy range of [0.01–1000] MeV. When using the Bethe equation to calculate the proton stopping power in the target elements, it was found that the greatest value was at the energy of 0.5 MeV, and a cutoff occurs at energy of 0.1 MeV in Al and 0.5 MeV in Si, Ag, Cu, Ge, Ag, Pt, Au, and Pb, but while using the Bohr equation, it is at an energy of 0.5 MeV in the elements Al, Si, Ag, Cu, Ge, Ag, Pt, Au, and Pb, and the cut occurs at an energy of 0.1 MeV in Al and 0.5 MeV in Si, Ag, Cu, Ge, Ag, Pt, Au, and Pb. The process varies in energy loss due to the nature and type of incident particles; these data can be used in many industrial applications. The stopping power of the Bohr and Bethe equations for the proton shell in these media was compared after programming them in MATLAB and using data from the SRIM 2012 program and data obtained from the PSTAR program. A semi-empirical equation was also extracted as a factor to multiply the Bohr equation so that its results were close to the PSTAR results for the electronic stopping force of the proton in the elements Al and Si within the energy range of 1–1,000 MeV, and the results were consistent with it. The experimental equations were extracted using curve fitting using the MATLAB language. For other elements within the same energy range, the results were consistent with the PSTAR results.